Guidelines for the medical management of pediatric vesicoureteral reflux. (1st April 2020) - Miyakita, Hideshi; Hayashi, Yutaro; Mitsui, Takahiko; Okawada, Manabu; Kinoshita, Yoshiaki; Kimata, Takahisa; Koikawa, Yasuhiro; Sakai, Kiyohide; Satoh, Hiroyuki; Tokunaga, Masatoshi; Naitoh, Yasuyuki; Niimura, Fumio; et al.
Abstract: Urinary tract infection is a bacterial infection that commonly occurs in children. Vesicoureteral reflux is a major underlying precursor condition of urinary tract infection, and an important disorder in the field of pediatric urology. Vesicoureteral reflux is sometimes diagnosed postnatally in infants with fetal hydronephrosis diagnosed antenatally. Opinions vary regarding the diagnosis and treatment of vesicoureteral reflux, and diagnostic procedures remain debatable. In terms of medical interventions, options include either follow‐up observation in the hope of possible spontaneous resolution of vesicoureteral reflux with growth/development or provision of continuous antibiotic prophylaxis based on patient characteristics (age, presence/absence of febrile urinary tract infection, lower urinary tract dysfunction and constipation). Furthermore, there are various surgical procedures with different indications and rationales. These guidelines, formulated and issued by the Japanese Society of Pediatric Urology to assist medical management of pediatric vesicoureteral reflux, cover the following: epidemiology, clinical practice algorithm for vesicoureteral reflux, syndromes (dysuria with vesicoureteral reflux, and bladder and rectal dysfunction with vesicoureteral reflux), diagnosis, treatment (medical and surgical), secondary vesicoureteral reflux, long‐term prognosis and reflux nephropathy. They also provide the definition of bladder and bowel dysfunction, previously unavailable despite their close association with vesicoureteral reflux, and show the usefulness of diagnostic tests, continuous antibiotic prophylaxis and surgical intervention using site markings.